Indústria cultural, educação escolar e currículo: a contradição ocultada e o desinteresse dos alunos pela educação formal - Silva, Cesar Augusto Alves da (2010)
There is, nowadays, a very significant amount of students in elementary and secondary public schools of São Paulo, attitudes that demonstrate a real lack of interest in formal education. This disinterest is observable when objectified in the classroom behaviors such as refusal to undertake activities related to reading and writing, violence against teachers, school buildings and their own colleagues, indiscipline and lack of concern with grades. For me, these attitudes are the outward and visible from a sociocultural process coming from a specific economic setting which totaled and thereby surreptitiously robbed the social power of men. Thus, the internal reason of the current socio-economic formation is directed not to men but to itself. This, not requiring individuals educated, but to consumers, only encourages the production of the latter. We believe that analyzing the attitudes and negative outcomes of students in public schools of São Paulo without taking into account the social background, economic and cultural in which they are immersed when out of public school institution is a huge mistake. Our research problem is to understand how the formation economic, social, cultural and contemporary was erected and organized itself to reach the point of influencing the students and cause them to lack of interest in formal education. Studying the causes of a lack of formal education for individuals and demonstrate that they are from their own economic and social scenario - which often calls itself this form of education as a remedy for all ills - it is at least indicative of the snare of the social contradiction . Furthermore, it is evidence of social reification which covered any theory that insists on the possibility of emancipation through education generating inclusion - that in itself is a contradiction in terms. To reach this level of understanding of the current scenario of lack of interest among students for formal education, we have the ideas and concepts of theorists such as Marx, Adorno, Marcuse, Benjamin and Horkheimer. These thinkers were critical to the elevation of a human and social phenomenon (the lack of students) the object of study verifiable and, especially, to understand their origins. We base ourselves in oral accounts of experiences in the classroom, by the author and fellow teachers in our region to work because they are experiencing verbal reports (ie, empirically) the situation of lack of interest among students for formal education in public schools state of São Paulo. However, the main source for our investigation was the very voice of the students, presented in interviews at the school where the author of this study teaches. Therefore, our hypothesis in this study is that the content and form of the culture engendered by industrial capitalism producer of goods, and imposed on each second to individuals, is diametrically opposed to the culture necessary and inherent to formal education in public schools